Pelatihan pengelolaan aset desa di Kecamatan Donri-Donri Kabupaten Soppeng - Muhammad Guntur; Muhammad Nur Yamin; Aslinda Aslinda (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
This activity aims to improve understandingregarding the management of village assets by the apparatus inevery village in the Donri-Donri District of Watansoppengdistrict. With this community service activity in the form ofVillage Asset management workshops, it is expected that themanagement of Village Assets by the local apparatus inaccordance with the Minister of Home Affairs Regulation No.1 of 2016 in terms of planning, procurement, use, utilization,security, maintenance, deletion, transfer, administration,reporting, assessment, guidance, supervision and control ofVillage Assets. The results of this community service show (1)Knowledge and understanding of village officials in DonriDonri District, Soppeng Regency increased compared tobefore training, especially in terms of managing village assetsin terms of planning, procurement, use, utilization, security,maintenance, removal, transfer, administration, reporting,assessment, guidance, supervision and control of VillageAssets. (2) Additional knowledge that is very useful for eachvillage apparatus to be able to improve their performance inthe implementation of their respective tasks.